Revestimentos de pectina adicionados de extrato hidroalcoolico de folhas de goiabeira (Psidium guajava L.): caracterização e aplicação em carne bovina fresca - Nascimento, Clarissa Pacheco Fernandes (2022)
This study aimed to develop pectin-based active edible coatings added with guava leaves (Psidium guajava L.) extract, to characterize and evaluate their effects when applied to fresh beef (Quadriceps femoris). First, a study was carried out based on an online questionnaire, on the perception of consumers regarding the use of edible coatings on fresh beef and the influence on the purchase and consumption habits of this product. From the guava leaves, hydroethanolics (70%) (HEGL) and aqueous (AEGL) extracts (leaves/extractor solution ration 1:25, w/v) were obtained, which were characterized in terms of total phenolic compoudns (TPC), total antioxidante activity (TAA) (ABTS and FRAP methods), antimicrobial activity (Staphylococcus aureus, Escherichia coli, and Salmonella typhimurium) and cytotoxicity. Then, formulations of pectin coatings added with the selected extract were prepared (1, 3 and 5%, v/v) and evaluated for TPC, TAA, color and rheological property. Then, the effect of the active pectin coating on the stability of fresh beef pieces was evaluated being analyzed for weight loss, firmness, pH, color, lipid oxidation (TBARS) and histological changes during 7 days of cold storage (4 °C). Online market research showed that most participants are confident in the potential of edible coatings for beef conservation, although They would like to know the product to draw their own conclusions. The studied extracts showed no antimicrobial and cytotoxic (0.001-100 μg/mL) activities. The HEGL showed higher TPC content (16.92 mg GAE/g od dry extract), in addition to higher TAA (240.73 μM Trolox/g of dry extract and 805.39 μM FeSO4/g of dry extract), which justified the incorporation of this extract in the coating. The coating with 5% extract showed high levels of TPC (10.23 mg GAE/g of coating), TAA (82.48 μM Trolox/g of coating, 167.57 μM FeSO4/g of coating), intensity of color and consistency index (k = 0.0504). Then, this formulation was selected for application on fresh beef. The coating contributed to minimize weight loss, tenderization, oxidative process (color and lipids) and tissue changes, promoting the maintenance of meat quality throughout the 7 days of storage. Therefore, the results revealed that the incorporation of the hydroethanolic extract of guava leaves provided antioxidant property to the pectin coating, which can be used in the conservation of fresh beef and adding value to this product by increasing its shelf life.